In Search of a Liturgical Patrimony: Anglicanism, Gallicanism & Tridentinism - Peter M. Doll (Revue Française de Civilisation Britannique)
In common with other churches of the Protestant and Catholic Reformations, the Church of England identified its own worship with that of the ancient Jewish Temple in Jerusalem and of the early Church. In the aftermath of Queen Mary’s restoration of Catholicism, the Church of England’s liturgical identity was also dominated by a severe Puritan reaction against all Catholic forms. In the last decade of Elizabeth’s reign, however, an ‘avant-garde’ of clergy emerged committed to greater ceremonialism in worship according to the Book of Common Prayer. The Laudian high churchmanship that emerged from this beginning was a movement in tension, looking simultaneously to the Patristic Church, the pre-Reformation Church in England (with a strong strain of ‘gothic survivalism’) and the even more risky world of the continental baroque. From the seventeenth to the nineteenth centuries, the Church of England was conscious of affinities with the Gallican, nationalist tradition in the French Church, but at either end of this period the Tridentine baroque would also prove seductively fascinating to many Anglicans. The use of the chancel screen was frequently a touchstone of this debate.While the Gallican tradition was effectively submerged within Roman Catholicism by the French Revolution and the First Vatican Council, the tension between the ‘Gallican’ and ‘Tridentine’ tendencies within Anglican high churchmanship remains alive to this day. In the nineteenth century, influential Anglican converts to the Church of Rome brought with them their contrasting convictions about the appropriate architectural setting for the liturgy. The architect A. W. N. Pugin, firmly committed to liturgical Gallicanism, advocated medieval music, architecture and Sarum ceremonial, while John Henry Newman and his fellow Oratorians insisted on an ultramontane liturgy and architecture. Through the creation of the Anglican Ordinariate within the Roman Catholic Church, the Anglican tradition continues to bear witness to the diversity of the Catholic tradition.